2017
DOI: 10.1039/c7ra08239h
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and high capacity lithium-ion battery anode based on a carbon nanotube/electrodeposited nickel sulfide paper-like composite

Abstract: A flexible NS@CNT composite is synthesized by electrodeposition, showing a record specific capacity in terms of the entire electrode mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The voltage range is separated by (i) lithiation process type, and (ii) the metal species involved. The observed extra capacity above theoretical was attributed to capacitive effects (known to occur for sulfide materials and other CAMs,,), as well as the contribution from the Cu 2‐x S film formed during ligand removal. The contribution of this film has been previously demonstrated to be initially significant, but diminishes rapidly with cycling …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The voltage range is separated by (i) lithiation process type, and (ii) the metal species involved. The observed extra capacity above theoretical was attributed to capacitive effects (known to occur for sulfide materials and other CAMs,,), as well as the contribution from the Cu 2‐x S film formed during ligand removal. The contribution of this film has been previously demonstrated to be initially significant, but diminishes rapidly with cycling …”
Section: Resultsmentioning
confidence: 89%
“…It can then be concluded that reporting the gravimetric capacity of a material over a wide voltage range (e. g., 0–2.5 V vs. Li/Li + ) is useful for investigating its lithiation characteristics, however this cannot be considered a meaningful assessment of its potential as a LIB anode. While this is particularly prevalent in the case of CAMs (binary, ternary and quaternary) due to their multi‐step lithiation nature, it is also applicable to single mode materials with relatively high discharge voltages such as Cu x S (discharges at 1.5–2 V vs. Li/Li +[9] ) or NiS x (discharges at ∼1.9–2.1 V vs. Li/Li +[56] ) which have been proposed as potential anodes ,,,…”
Section: Resultsmentioning
confidence: 99%
“…NiS nanoparticles electrodeposited on CNT lm was utilized in order to obtained NiS NPs/CNT paper-like high capacity exible LIBs anode. 26 The composite anode can tolerate the mechanical stress without any structural failure via a simple in situ hydrolysis method, then freeze-drying followed by annealing at 500 C. 42 The highly porous nature of this electrode helps to sufficient amount of electrolyte inltration and buffer the volume change of TiO 2 , which leads to a high specic capacity of 234 mA h g À1 at 50 mA g À1 , excellent rate performance (149 mA h g À1 at 2000 mA h g À1 ), and remarkable cycling stability (210 mA h g À1 at 100 mA g À1 at the 100 th cycles). Moreover, at 91% compressible strain, the anode can be able to sustain structural intactness aer releasing from 10 times of volumetric compressed state.…”
Section: Carbon Nanotube (Cnt) Supported Electrodesmentioning
confidence: 99%
“…Thus, this process can be used for the measurement of R due to the bending condition is controlled by an automated machine with uniform distribution of stress and variation speed of bending angle that can be Fig. 8 Highest initial capacity at the certain current density of (a) CNT, [24][25][26]30,31,33,36,39,40,[42][43][44]48 (b) CNFs, 52,[55][56][57][58][59][60][62][63][64][65][66][67][68][69][70][71][72][73][74][75]77,78 (c) graphene, [85][86][87][90][91][92][93][94][95][96][97][98]…”
Section: Techniques For Mechanical Deformation Evaluationmentioning
confidence: 99%
“…Among the battery types, LIBs, including lithium secondary batteries, have been widely used because of their good power and energy densities, high rate capability, and high level of safety . In recent years, many studies on nickel sulfide greatly benefitted the development of lithium batteries .…”
Section: Introductionmentioning
confidence: 99%